Towards new botanical pesticides: the toxic effect of Eremanthus goyazensis (Asteraceae) leaves essential oil against Brevipalpus phoenicis (Acari: Tenuipalpidae) - Baldin, Edson Luiz Lopes [UNESP]; Souza, Efrain S. [UNESP]; Silva, José Paulo G. F. [UNESP]; Pavarini, Daniel P.; Lopes, Norberto P.; Lopes, João L. C.; Souza, Gustavo H. B. (Sociedade Brasileira de Química, 2012)
This work reports the chemical characterization of Eremanthusgoyzensis essential oil and its toxic effect over Brevipalpus phoenicis. The essential oil displayed a major composition of sesquiterpenes (61.87%) including trans-caryophillene (26.81%) and germacrene-D (13.31%). The fumigation test indicated a promising bioactivity over adult B. phoenicis individuals at 24 h (2.03 µL/L of air) and 48 h (1.08 µL/L of air) of exposition. A brief discussion of essential oils composition and their singular role on the toxic effect over B. phoenicis is provided here. Our results may contribute to a new and profitable use of a species of Brazilian flora on agribusiness.
Keywords: Asteraceae; red and black flat mite; botanical pesticide